Laser-induced graphenization of textile yarn for wearable electronics application. (24th August 2021) - Parmeggiani, Matteo; Stassi, Stefano; Fontana, Marco; Bianco, Stefano; Catania, Felice; Scaltrito, Luciano; Lamberti, Andrea
Abstract: The present paper deals with the selective laser writing of textile yarns in order to induce a conductive path useful for smart textiles application. The incident power of the laser induces a conversion of an aramid fiber surface into graphene-based conductive material with tunable electrical properties depending on the laser writing parameters. The physical-chemical properties of the resulting smart yarns have been intensively characterized by electron microscopy, Raman spectroscopy, electrical and mechanical investigations. The results confirm the few-layer graphene fingerprint of the written paths onto the textile yarn with suitable properties for their application into electronic textiles. Indeed, a yarn-shape strain sensor with excellent performance has been developed and characterized to demonstrate the potential application of the proposed technology to the wearable electronic field.